2008
DOI: 10.1176/appi.ajp.2008.07101640
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion Tensor Imaging Findings in First-Episode and Chronic Schizophrenia Patients

Abstract: The cross-sectional data reported here suggest less widespread changes in white matter at illness onset in schizophrenia which progress in more chronic states. More definitive conclusions will require follow-up imaging of first-episode schizophrenia patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
170
4
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 229 publications
(196 citation statements)
references
References 39 publications
20
170
4
2
Order By: Relevance
“…Diffusion-weighted imaging has been relatively consistent in reporting reduced callosal FA in chronic schizophrenia (Douaud et al, 2007;Koch et al, 2010;Kubicki et al, 2008;Miyata et al, 2010;Mori et al, 2007b;RotarskaJagiela et al, 2008), including during remission (Koch et al, 2010) and less consistently in studies examining individuals at the first episode (Cheung et al, 2008;Gasparotti et al, 2009;Perez-Iglesias et al, 2010b;Peters et al, 2008;Price et al, 2005;Szeszko et al, 2005) or in earlier stages of illness (Davenport et al, 2010;Douaud et al, 2007;Kyriakopoulos and Frangou, 2009). Directly comparing first episode and chronic groups supports more severe changes in FA in the genu of the corpus callosum (Friedman et al, 2008;Kong et al, 2011), the left ILF (Friedman et al, 2008), and ALIC (Bora et al, 2011) in the chronic group including relative to the first episode group. By contrast, the large scale metaanalysis by Bora et al (2011) has reported the opposite, specifically for the genu of the corpus callosum, with FA being lower in the first episode relative to the chronic group with schizophrenia.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Diffusion-weighted imaging has been relatively consistent in reporting reduced callosal FA in chronic schizophrenia (Douaud et al, 2007;Koch et al, 2010;Kubicki et al, 2008;Miyata et al, 2010;Mori et al, 2007b;RotarskaJagiela et al, 2008), including during remission (Koch et al, 2010) and less consistently in studies examining individuals at the first episode (Cheung et al, 2008;Gasparotti et al, 2009;Perez-Iglesias et al, 2010b;Peters et al, 2008;Price et al, 2005;Szeszko et al, 2005) or in earlier stages of illness (Davenport et al, 2010;Douaud et al, 2007;Kyriakopoulos and Frangou, 2009). Directly comparing first episode and chronic groups supports more severe changes in FA in the genu of the corpus callosum (Friedman et al, 2008;Kong et al, 2011), the left ILF (Friedman et al, 2008), and ALIC (Bora et al, 2011) in the chronic group including relative to the first episode group. By contrast, the large scale metaanalysis by Bora et al (2011) has reported the opposite, specifically for the genu of the corpus callosum, with FA being lower in the first episode relative to the chronic group with schizophrenia.…”
Section: Discussionmentioning
confidence: 95%
“…In WM, a single study of individuals experiencing their first psychotic episode did not detect microstructural changes (as assessed by DTI) in the corpus callosum relative to healthy controls (Price et al, 2005). Studies including both first episode and chronic patients showed that patients with chronic disease had significantly reduced FA compared with controls, reaching only a trend level in first episode patients (Friedman et al, 2008;Kong et al, 2011). This implies a progressive nature associated with illness duration in schizophrenia, as previously reported in a structural study investigating GM and WM volumes reporting a progressive reduction in the frontal WM volume in patients (Ho et al, 2003).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…12 This hypothesis is consistent with the result of another DTI investigation of a large cohort of patients withˆrst-episode schizophrenia, which conˆrmed a reduction of FA in the inferior longitudinal fasciculus alone. 13 Patients with schizophrenia also demonstrate abnormalities of the semantic network, which are identiˆed by DTI analysis as a decrease of signiˆcant FA in the left inferior frontal white matter and are revealed by functional MR imaging as weaker connectivity between the left inferior frontal gyrus and left middle temporal gyrus. 14 Furthermore, in a 15-month study of youths (mean age: 17.02±3.37) at high risk for psychosis, TBSSbased ROI analysis revealed a signiˆcant relationship between lower baseline FA values in the medial temporal lobe and inferior longitudinal fasciculus and deterioration of social and role functioning, whereas the normal progressive increase of FA with age was not seen.…”
Section: Schizophreniamentioning
confidence: 99%
“…Disruptions in WM tract structures have been consistently implicated in the pathophysiology of schizophrenia; a number of diffusion tensor imaging (DTI) studies in schizophrenia have implicated WM abnormalities in various brain regions. [6][7][8][9][10] Although there is a lack of consistency in the spatial localization of the brain regions showing reduced fractional anisotropy (FA), 11 in this regard it has been found that WM abnormalities are not localized to a specific brain region but instead reflect a diffuse process with widely dispersed focal reductions in FA that vary spatially among individuals. [12][13][14] Of all the DTI parameters examined so far, FA of water diffusion has the highest reported heritability.…”
Section: Introductionmentioning
confidence: 99%